2021
DOI: 10.1002/mp.14774
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Dose prediction for radiation therapy using feature‐based losses and One Cycle Learning

Abstract: To present the technical details of the runner-up model in the open knowledge-based planning (OpenKBP) challenge for the dose-volume histogram (DVH) stream. The model was designed to ensure simple and reproducible training, without the necessity of costly advanced generative adversarial network (GAN) techniques. Methods: The model was developed based on the OpenKBP challenge dataset, consisting of 200 and 40 head-and-neck patients for training and validation, respectively. The final model is a U-Net with addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The rough comparison results showed that the proposed model performance (MAE = 2.43 Gy) was competitive to that proposed by Liu et al 38 (MAE = 2.31 Gy) using Cascade 3D U-Net, which achieved the first place in the OpenKBP competition. Moreover, it was superior to the second-ranked method proposed by Gronberg et al 37 (MAE = 2.56 Gy) using 3D dense dilated U-Net, and the third-ranked method proposed by Zimmermann et al 41 (MAE = 2.62 Gy) using GAN. Also, a rough comparison was made to other dose prediction methods in the literature where the assessment process is typically similar to what we used in this study with the MAE calculated over all voxels within the body contour.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The rough comparison results showed that the proposed model performance (MAE = 2.43 Gy) was competitive to that proposed by Liu et al 38 (MAE = 2.31 Gy) using Cascade 3D U-Net, which achieved the first place in the OpenKBP competition. Moreover, it was superior to the second-ranked method proposed by Gronberg et al 37 (MAE = 2.56 Gy) using 3D dense dilated U-Net, and the third-ranked method proposed by Zimmermann et al 41 (MAE = 2.62 Gy) using GAN. Also, a rough comparison was made to other dose prediction methods in the literature where the assessment process is typically similar to what we used in this study with the MAE calculated over all voxels within the body contour.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, it was superior to the second‐ranked method proposed by Gronberg et al 37 . (MAE = 2.56 Gy) using 3D dense dilated U‐Net, and the third‐ranked method proposed by Zimmermann et al 41 . (MAE = 2.62 Gy) using GAN.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Every dose prediction model used a neural network architecture that was based on either a U-Net [23], V-Net [24], or Pix2Pix [25] architecture. Many of the best performing models also used other generalizable techniques like ensembles [26], one-cycle learning [27], radiotherapy-specific loss functions [28], and deep supervision [29].…”
Section: B Developing Dose Prediction Modelsmentioning
confidence: 99%
“…The DL-based methods perform well in automatic feature extraction and mapping transformation (5,8). The dose prediction model can make an end-to-end mapping transformation between patients' anatomical and dose distribution information with organs-atrisk (OARs) constraints (9)(10)(11)(12). Compared with using the conventional treatment planning system (TPS), using the DL model to generate predicted dose distribution reduces planning time significantly (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%